Advances in Greek generative syntax : in honor of Dimitra Theophanopoulou-Kontou - Theophanopoulou-Kontou, Dēmētra; Stavrou, Melita; Terzi, Arhonto (Linguistik aktuell ;, 2005)
This collection of original research focuses on various lesser studied aspects of Greek syntax. The articles combine a sound empirical coverage within current developments of generative theory and cover a wide spectrum of areas. The syntax of sentential structure is dealt with by two articles, one is an extensive analysis of the distribution of goal and beneficiary dative DPs in Greek (and cross-linguistically) and the other addresses the relation agree in small clauses (and between adjectives and nouns). Two articles study the acquisition of the left periphery and of eventivity and one focuse.